Constitution and Constitutionalism of Indonesia - Sri Praptini Praptini; Sri Kusriyah Kusriyah; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The term constitution comes from a constituer which means to form, that is , the whole of the rules both written and unwritten which regulate in a binding manner the way a government is held in a society. Constitutionalism in the strict sense is that the administration of the government which islimited by the Constitution, in a broad sense, is a set of political values and aspirations that reflect the desire to protect freedom by carrying out internal and external supervision of government power.There are differences and similarities in the four constitutional ions in Indonesia: a) Procedural aspects: only in the 1945 Constitution, as written and unwritten basic law, are flexible and rigid to adopt the supreme constitution, procedures for establishing and forming by the MPR, other written constitutions; RIS by the Constitutional Assembly, 1950 Constitution by the Constituent Assembly; RIS changes to the constitution with the Federal Law while the 1950 Constitution by the Assembly changes the Constitution; b) Substantial aspects, the form of the Unitary state existed in the 1945 Constitution before and after the changes and the 1945 Constitution, while the RIS of union states, all forms of republic government, recognition of human rights, the system of government of the 1945 Constitution before and after quasi presidential and presidential changes, while RIS and The 1950 Constitution of the Republic of Indonesia, the 1945 Constitution before the change of the highest sovereignty holders of the MPR, the RIS by the Government together with the DPR and the Senate, the 1950 Constitution by the Government and Parliament.Keywords: Constitution; Constitutionalism; Indonesian Constitution.